Correlation between Hormonal Imbalances and Adult Female Acne - Ullah, Naimat; Bhojwani, Sandia; Juriasinghani, Manesha; Khan, Ihsanullah (Journal of Neonatal Surgery, 2024)
Background: Acne in adult women is increasingly viewed as being linked with underlying hormonal and metabolic dysfunctions, rather than being merely a problem with the skin itself. Many women suffering from chronic acne have mild and perhaps undiagnosed endocrine abnormalities. Objectives: To examine the relationship between hormonal imbalances and acne severity in adult females and to identify which hormonal markers show the strongest associations. Methods: From February 2023 until February 2024, a cross-sectional study was carried out in which 82 women of different age groups and levels of acne were recruited. Data collected were clinical examination, menstruation history, anthropometry, and focused hormonal assays such as testosterone, SHBG, DHEAS, LH/FSH ratio, prolactin, TSH, fasting insulin, and HOMA-IR were conducted. It was determined based on a standardized grading system the severity of acne was graded on. ANOVA, Chi-square, and Spearman correlation statistical tests were performed. Results: Increased severity of acne was always concomitant with increased total and free testosterone with increased DHEAS and higher LH/FSH ratios and SHBG levels. Insulin resistance also increased steadily with increased severity. In cases of moderate and severe acne, the prevalence of these conditions was highly apparent for menstrual irregularity and PCOS characteristics. Conclusions: Several studies have found that specific hormonal imbalances, especially increased androgen levels and insulin resistance, are closely related to the severity of adult female acne. Recognizing the severity of the condition to focus on the target for the specific management of the condition could be of help..